Multiple micronutrient supplementation in Tanzanian infants born to HIV-infected mothers: a randomized, double-blind, placebo-controlled clinical trial(1)(2)(3)(4) - Duggan, Christopher (American Society for Nutrition, 2012)
Background: Multiple micronutrients (vitamin B complex and vitamins C and E) were effective at reducing infectious disease morbidity, HIV disease progression, and poor pregnancy outcomes in HIV-infected women. Objective: The objective was to evaluate whether direct supplementation of these micronutrients to HIV-exposed infants reduces mortality and morbidity. Design: Infants born to HIV-infected women from Dar es Salaam, Tanzania, were randomly assigned to receive daily oral supplementation of multiple multivitamins (vitamin B complex and vitamins C and E) or placebo from age 6 wk for 24 mo. All-cause mortality, hospitalizations, and unscheduled clinic visits were recorded. Morbidities were recorded during monthly follow-up visits. All mothers received multiple micronutrients throughout the study. Results: A total of 1193 infants were randomly assigned to receive micronutrients and 1194 to receive placebo. There were 138 child deaths in the multivitamin group and 124 deaths in the placebo group (HR: 1.13; 95% CI: 0.88, 1.44; P = 0.33). Hospitalizations (RR: 0.83; 95% CI: 0.62, 1.13; P = 0.23), unscheduled clinic visits (RR: 0.97; 95% CI: 0.85, 1.10; P = 0.59), and maternal reports of diarrhea (RR: 0.97; 0.87, 1.10; P = 0.64) were not significantly different between the 2 groups. Fever (P = 0.02) and vomiting (P = 0.007) were significantly lower in the multivitamin group. Among 429 children whose mothers received antiretroviral (ARV) therapy, multivitamin use had no effect on mortality but was associated with a significant reduction in hospitalizations (P = 0.035), episodes of fever (P = 0.005), and episodes of fever and cough (P = 0.019). Conclusions: In the setting of maternal micronutrient supplementation, supplementation of HIV-exposed infants with vitamin B and vitamins C and E does not reduce mortality. Studies of nutrition supplementation in ARV-exposed infants may be warranted. This trial was registered at clinicaltrials.gov as NCT00197730.